Design of a cosine pulse transceiver operating in the discrete-time domain - Berber, Stevan M. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: The paper presents the theory and the design issues of a transceiver for a discrete-time cosine pulse transmission. The operation of the transceiver and all signals are analyzed in both time and frequency domains.Methods: The detailed theoretical models of the transmitter and the receiver are presented based on their block schematics expressed in terms of mathematical operators. The transceiver blocks are simulated and the results of their simulation are presented and compared with the theoretical results.Results: Discrete-time signals at the input and the output of each transceiver block are derived in the mathematical form and presented in the time and frequency domain. A transceiver simulator is developed in Matlab. The simulation results confirmed the theoretical findings.Conclusion: The results of this work contribute to the theoretical modeling and design of modern transceivers that can be used for discrete-time cosine pulse transmission.
Keywords: transceiver design; discrete cosine pulse; pulse transceiver; transceiver mathematical modeling; filtering; transceiver simulation